Cultivo de la uva en El Salvador - Alvarenga Reyes, Carlos Orlando (Estelí (Nicaragua), 1978)
Sumario (Es)
Ilus.; 4 ref.
Tesis (Tec Agr)
Keywords: UVA; CULTIVO; CLIMA; RIEGO; VARIEDADES; APLICACION DE ABONOS; PODA; PLAGAS; ENFERMEDADES DE LAS PLANTAS; COSECHA; EL SALVADOR; NICARAGUA